A life on our planet : [large type] my witness statement and a vision for the future - Attenborough, David, 1926-; Hughes, Jonnie (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"In this scientifically informed account of the changes occurring in the world over the last century, award-winning broadcaster and natural historian shares a lifetime of wisdom and a hopeful vision for the future. See the world. Then make it better. I am 93. I've had an extraordinary life. It's only now that I appreciate how extraordinary. As a young man, I felt I was out there in the wild, experiencing the untouched natural world - but it was an illusion. The tragedy of our time has been happening all around us, barely noticeable from day to day -- the loss of our planet's wild places, its biodiversity. I have been witness to this decline. A Life on Our Planet is my witness statement, and my vision for the future. It is the story of how we came to make this, our greatest mistake -- and how, if we act now, we can yet put it right. We have one final chance to create the perfect home for ourselves and restore the wonderful world we inherited. All we need is the will to do so"--